UniCa PhD Book - XXXIII Cycle - Ruggerone, Paolo; Pelligra, Vittorio (UniCa PhD Books, 2020)
This volume reports, in brief, the experience of the students enrolled in the XXXIII cycle of the PhD courses at the University of Cagliari. The contributions are grouped by course and are preceded by a presentation of the coordinators of each PhD program. In two pages each student gives the reader an idea of his/her personal experience and of the results of his/her research.